Does Surface or Subsurface Tillage Influence Burley Tobacco Yield, Leaf Temperature, or Alkaloid Content?. Issue 1 (20th February 2015) - Ritchey, Edwin L.; Pearce, Robert C.; Grove, John H.
Abstract : Transplanted crop growth can be adversely affected by soil compaction. Subsoil tillage is commonly used when compaction is suspected. No‐tillage (NT) fields are often thought to be compacted although this is seldom confirmed by soil bulk density (BD) before subsoiling. The objectives of this study were to investigate the effects of surface and subsurface tillage on tobacco ( Nicotiana tabacum L.) yield, soil BD, leaf temperature, and leaf alkaloids; and to correlate tobacco leaf temperature, leaf alkaloid levels, and soil BD with root‐caused yield limitations. In five trials, surface tillage main plots consisted of NT and conventional moldboard tillage (CT), with the absence/presence of subsoiling as subplots. Soil BD values were influenced by tillage and varied with site‐year and sampling depth. They were also influenced by sampling location and the surface traffic pattern, but were not yield limiting. The CT system favored yield in three of five site‐years by 6 to 38%, but yield was not influenced by subsoiling. Tobacco leaf temperature was 2.4 to 3.3% lower in the NT treatments when differences were observed, but did not translate into higher yields relative to the CT treatments. Leaf alkaloid content was 5.6 to 23.8% higher in CT treatments. Percent conversion of nicotine to nornicotine was 18.5% greater in CT treatments. Simple linear regression indicated that leaf temperature, BD, and leaf alkaloids were related to yield, but not consistently. Although results suggest that greater CT yields were related to greater root exploration, additional research is needed to fully understand the relationships involved.